1997
DOI: 10.4319/lo.1997.42.5.0800
|View full text |Cite
|
Sign up to set email alerts
|

Interannual changes in seagrass (Posidonia oceanica) growth and environmental change in the Spanish Mediterranean littoral zone

Abstract: The inter-annual changes in leaf formation and vertical growth rates and their correlation to the records available of environmental change (rainfall, mean sea level, water temperature, and transparency) were examined in 15 Posidonia oceanica meadows growing along the Spanish Mediterranean coast between 1967 and 1992. P. oceanica leaf production fluctuated interannually, but it did not exhibit any steady trend toward decline, indicative of nonhuman effects on changes in water quality in these areas. Conversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 18 publications
(18 reference statements)
5
77
1
Order By: Relevance
“…Although incidences of high short-term rainfall and flooding have commonly resulted in detrimen- CSIRO 2007, Suppiah et al 2007 tal effects on seagrass meadows (Campbell & McKenzie 2004, Cardoso et al 2008, terrestrial water flows are important in supplying nutrients into coastal seagrass meadows (Short 1987, Udy et al 1999. Therefore, these findings are similar to those for temperate seagrasses (Marba & Duarte 1997) and suggest that the periods of drought that were experienced between 2002 and 2006, when the Norman River almost completely stopped flowing, may have been detrimental by not supplying sufficient nutrients to seagrass meadows. Alternative explanations for the positive effect of river flow could also relate to the effect of salinity on the germination of seeds (Orth et al 2000).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although incidences of high short-term rainfall and flooding have commonly resulted in detrimen- CSIRO 2007, Suppiah et al 2007 tal effects on seagrass meadows (Campbell & McKenzie 2004, Cardoso et al 2008, terrestrial water flows are important in supplying nutrients into coastal seagrass meadows (Short 1987, Udy et al 1999. Therefore, these findings are similar to those for temperate seagrasses (Marba & Duarte 1997) and suggest that the periods of drought that were experienced between 2002 and 2006, when the Norman River almost completely stopped flowing, may have been detrimental by not supplying sufficient nutrients to seagrass meadows. Alternative explanations for the positive effect of river flow could also relate to the effect of salinity on the germination of seeds (Orth et al 2000).…”
Section: Discussionsupporting
confidence: 73%
“…Long-term studies directly measuring seagrass changes and how they are correlated with climate are rare. Such studies are restricted to the Mediterranean Sea and coastal areas of Florida (Marba & Duarte 1997, Tomasko et al 2005; no similar studies have been reported for the tropical Indo-Pacific region.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…metoffice.gov.uk; Scientific Electronic Library Online of the National Commission of Scientific and Technological Research of Chile, scielo.cl; Smithsonian National Museum of Natural History, www.nmnh.si.edu; and Ministry of Culture of China, www. chinaculture.org) and published and unpublished records of sea surface temperature at the region where marine populations grew (29)(30)(31), respectively (SI Table 2). …”
Section: Materials and Methods Data Compilationmentioning
confidence: 99%
“…For instance, similar rates of warming have been reported in the Mediterranean, with comparable impacts on populations of Posidonia oceanica (between 1967 andMarbà and Duarte 1997;Jordà, Marbà, and Duarte 2012). Olsen et al (2012) documented the impacts of warming from 25°C to 32°C on Posidonia oceanica and Cymodocea nodosa from the Mediterranean Sea, reporting reduced rates of growth, leaf formation, and leaf biomass per shoot.…”
Section: A Warming Estuarymentioning
confidence: 78%